2020
DOI: 10.1038/s41598-020-61820-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the winter temperature regime on survival, body mass loss and post-winter starvation resistance in laboratory-reared and field-collected ladybirds

Abstract: Ongoing climate change results in increasing temperatures throughout the seasons. The effects of climate change on insect performance are less studied during the winter season than during the growing season. Here, we investigated the effects of various winter temperature regimes (warm, normal and cold) on the winter performance of the invasive ladybird Harmonia axyridis (Coleoptera: Coccinellidae). Winter survival, body mass loss and post-winter starvation resistance were measured for a laboratoryreared popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 56 publications
(81 reference statements)
1
13
0
Order By: Relevance
“…Note that high winter mortality of laboratory-reared beetles resulted in a limited number of individuals sampled in the last period, that is, after overwintering, especially for the cold winter treatment (n warm = 36, n average = 33, n cold = 12; see our dataset in Supporting Information Table S3). In our previous study (Knapp and Řeřicha 2020), we showed that winter survival was significantly lower for laboratory-reared compare to field-collected ladybirds. We suppose that environmental stability experienced during ladybird development or food quality, for example, Ephestia egg diet can limit ladybird capacity to produce cryoprotectants, may be responsible for this pattern.…”
Section: Experiments 1 (Laboratory-reared Beetles)mentioning
confidence: 72%
See 4 more Smart Citations
“…Note that high winter mortality of laboratory-reared beetles resulted in a limited number of individuals sampled in the last period, that is, after overwintering, especially for the cold winter treatment (n warm = 36, n average = 33, n cold = 12; see our dataset in Supporting Information Table S3). In our previous study (Knapp and Řeřicha 2020), we showed that winter survival was significantly lower for laboratory-reared compare to field-collected ladybirds. We suppose that environmental stability experienced during ladybird development or food quality, for example, Ephestia egg diet can limit ladybird capacity to produce cryoprotectants, may be responsible for this pattern.…”
Section: Experiments 1 (Laboratory-reared Beetles)mentioning
confidence: 72%
“…Unfortunately, a low number of experimental studies investigating the effects of winter period on immune responses do not allow us to make generalizations that lead to particular patterns. As temperate insects are facing a limited energy budget during overwintering (Ferguson et al 2018a, Knapp andŘeřicha 2020), decreasing haemocyte concentrations through the winter could be linked to the high energetic costs of cellular immunity maintenance compared to humoral immunity (Ferguson et al 2016). Note that stress in the form of limited energy sources caused by starvation, results in a reduced haemocyte F I G U R E 3 Sex-specific effects of overwintering on total protein concentration in the field-collected Harmonia axyridis ladybirds.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations